2020
DOI: 10.1007/s42399-020-00515-6
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in COVID-19: Is it Rational? A Systematic Review and Meta-Analysis

Abstract: Due to a lack of definitive treatment, many drugs were repurposed for Coronavirus disease (COVID-19) treatment; among them, corticosteroid is one. However, its benefit or harm while treating COVID-19 is not fully studied. Thus, we conducted this meta-analysis to assess the rationality on the use of corticosteroids in COVID-19. Pubmed, Medline, Clinicaltrials.gov, Cochrane library, and Preprint publisher were searched. In the qualitative syntheses, 41, and quantitative studies, 40, were included using PRISMA gu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…As of writing this manuscript (early November 2020), 16 meta-analyses 3,[104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] have examined the use of glucocorticoids in patients with COVID-19 or coronavirus infections. Regarding mortality, 4 metaanalyses 3,106,111,112,117 included RCTs (1 including 7 RCTs, 3 including 1 or 2 RCTs) and the rest only included observational studies.…”
Section: Principal Ndings and Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As of writing this manuscript (early November 2020), 16 meta-analyses 3,[104][105][106][107][108][109][110][111][112][113][114][115][116][117][118] have examined the use of glucocorticoids in patients with COVID-19 or coronavirus infections. Regarding mortality, 4 metaanalyses 3,106,111,112,117 included RCTs (1 including 7 RCTs, 3 including 1 or 2 RCTs) and the rest only included observational studies.…”
Section: Principal Ndings and Comparison With Other Studiesmentioning
confidence: 99%
“…Regarding mortality, 4 metaanalyses 3,106,111,112,117 included RCTs (1 including 7 RCTs, 3 including 1 or 2 RCTs) and the rest only included observational studies. Of these meta-analyses, 5 3,[104][105][106][107] found that glucocorticoids treatment decreased all-cause mortality, 7 [108][109][110][111][112][113][114] found no association between glucocorticoids treatment and allcause mortality, and the others [115][116][117][118] found glucocorticoids treatment increased all-cause mortality. In general, meta-analyses that supported glucocorticoids treatment mostly identi ed studies on COVID-19 patients who were severely-ill or with ARDS.…”
Section: Principal Ndings and Comparison With Other Studiesmentioning
confidence: 99%
“…According to this review, dexamethasone has been considered as a standard in the treatment of COVID-19, especially in severe cases, since a study conducted in the UK showed a 35% reduction in mortality rate in patients with mechanical ventilation and a 20% reduction in the mortality rate in patients who were given oxygen [ 38 ]. In contrast, a recent meta-analysis questioned the efficacy of corticosteroids in COVID-19, concluding that “with the use of corticosteroids, delayed recovery and a longer hospital stay were observed” [ 39 ]. Together with dexamethasone, remdesivir has been authorized and recommended for the therapy of COVID-19 in the US, where two studies have shown that this drug accelerated the patient’s recovery compared to placebo, and reduced hospitalization period [ 37 ].…”
Section: Discussion Conclusion and Future Directionsmentioning
confidence: 99%
“…Table 3 summarizes the characteristics and main finding from 13 systematic reviews and meta-analyses published since March 2020 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 . Two of these systematic reviews included only randomized controlled trials 76 , 77 .…”
Section: Summary Of the Clinical Evidence Of Corticosteroids Effects mentioning
confidence: 99%